PsycEXTRA Dataset 2004
DOI: 10.1037/e566402006-001
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Technology Surveillance - United States, 2001

Abstract: Problem/Condition: Since the first U.S. infant conceived with assisted reproductive technology (ART) was born in 1981, both the use of ART and the number of fertility clinics providing ART services have increased steadily in the United States. ART includes fertility treatments in which eggs or embryos are handled in the laboratory (i.e., in vitro fertilization [IVF] and related procedures). Women who undergo ART procedures are more likely than women who conceive naturally to deliver multiple-birth infants. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
196
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(208 citation statements)
references
References 17 publications
5
196
1
6
Order By: Relevance
“…Some studies previously reported lower conception rates in PCOS women undergoing ovulation induction [42]. This could not be confirmed in the current study, especially when compared with mean pregnancy rates after ICSI per transfer in the European (28.7%) and American studies (41%) [43,44]. Although miscarriage rate in our study did not differ between both studied groups, we observed tendency to higher number of miscarriages in GnRH antagonist than in GnRH agonist group (18% vs. 8%, respectively).…”
Section: Discussioncontrasting
confidence: 92%
“…Some studies previously reported lower conception rates in PCOS women undergoing ovulation induction [42]. This could not be confirmed in the current study, especially when compared with mean pregnancy rates after ICSI per transfer in the European (28.7%) and American studies (41%) [43,44]. Although miscarriage rate in our study did not differ between both studied groups, we observed tendency to higher number of miscarriages in GnRH antagonist than in GnRH agonist group (18% vs. 8%, respectively).…”
Section: Discussioncontrasting
confidence: 92%
“…Additionally, patients often view their involve-ment with the physician at the time of key procedures to be a marker of success or "good luck" for that procedure. As in vitro fertilization (IVF) gains increased utilization [1], efficiency of a busy IVF unit requires a team physician approach that involves multiple physicians being involved in the course of a patient's cycle and procedures. This process may seem daunting to patients who are familiar with a specific physician's care.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was focused on singleton births only, so the results and conclusion should be interpreted with caution due to exclusion of previously confirmed increased incidence of preterm and multiple births in IVF pregnancies (4,6,(16)(17)(18)(19)(20)(28)(29)(30)(31).…”
Section: Scientific Journal Of the Faculty Of Medicine Inmentioning
confidence: 99%
“…Since then, more than two million babies have been delivered worldwide through the use of ART procedures (2). In vitro fertilization treatment alone now accounts for an estimated 1% of all births in the United States of America (3,4) and 1% to 4% of births in European countries (5) with a proven increase of the percentage of IVF singletons and twins from 1.4% in 1995 to 3.0% in 2000, with an average of 2.3% (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation